P–453 Fertility preservation in endometriosis: Impact of the ovarian endometriosis and it's surgical treatment on oocyte yield. (6th August 2021) - Maget, A S; Bourdon, M; Salle, B; Patrat, C; Maignien, C; Marcellin, L; Chapron, C; Santulli, P
Abstract: Study question: Does a previous history of surgery for ovarian endometriosis (OMA) has an impact on controlled ovarian stimulation (COS) response in case of fertility preservation (FP) for endometriosis? Summary answer: After COS, a prior history for OMA surgery was associated with poorer ovarian responsiveness compared to non-previously operated women. What is known already: Endometriosis is a chronic disorder that affects 10% of woman, which can be responsible for infertility. The presence of OMA and/or it's excision could induce a reduction of the ovarian reserve (ROR), and for some women, an increased risk of premature ovarian failure. Therefore, FP with oocyte/embryo vitrification can be proposed for OMA-affected women, considering the relationship between endometriosis, infertility and ROR. Although a complete surgery excision of endometriosis lesions may be appropriate for some patients to relieve them from pain, the more efficient time to preserve fertility is still unknown in the management of women presenting OMA lesions. Study design, size, duration: We conducted an observational multicentric study from April 2015 to December 2019, in two tertiary care university hospitals. Women presenting OMA or having a previous history of surgery for OMA that had performed a FP with COS for oocytes/embryo vitrification during the study period were included. Diagnosis of endometriosis was based on published imaging criteria using transvaginal sonography and magnetic resonance imaging or histologically proven in women who had past surgery. Participants/materials, setting, methods: A total of 165 women were allocated to two groups, according to the presence of a previous history of surgery for endometrioma(s). Main outcome measure was the total number of oocytes retrieved. Main results and the role of chance: Fifty-one (30, 9%) women were included in the group 'previous history of surgery' and 115 (69, 1%) in the group 'no history of surgery'. Mean age was 31, 6±4, 4 years and was not significantly different between groups (p = 0.09). However, women in 'No previous surgery' group had higher AMH levels than women in 'previous surgery' group (2.27±1.70ng/ml versus 1.56±1.89ng/ml; p < 0, 001). In the group 'previous history of surgery', 21(41.2%) women had a recurrence of OMA(s) and 31 (60.8%) had at least one deep infiltrating endometriosis (DIE) lesion at FP. In the group 'no history of surgery', 92(80.7%) of the women had DIE. In addition, women in 'No previous surgery group' had larger OMA than women in 'previous surgery' group (mean diameter size: 5.56±4.34cm versus 3.25±2.16cm, respectively; p:0, 03). The mean number of COS with oocyte-retrieval was significantly higher in the group 'previous history of surgery' (2.0±1.02 versus 1.65±0.82 in the group 'no surgery', p = 0.03), however, the total number of oocytes retrieved per women was significantly higher in women 'history of surgery', compared to women 'no previous surgery' (13.7±8.4 versus 10.3±7.5, p = 0.02). In addition, the cancellation rate per cycle was significantly lower in 'No previous surgery' group compared to the 'previous surgery' group (0.09±0.31 versus 0.28±0.53; p < 0.001). Limitations, reasons for caution: No data concerning the thawing of oocytes/embryo are available for now. Wider implications of the findings: FP is an essential component to integrate in ovarian endometriosis-management and should be proposed before surgery to optimize oocyte yield. Trial registration number: Not applicable